2020
DOI: 10.23887/jpi-undiksha.v9i2.17480
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Affects Students’ Attitude and Conceptual Understanding in Learning 3d Geometry

Abstract: The study investigates the impact of using AR in learning 3D geometry on students’ attitudes and conceptual understanding. The research was carried out using a quasi-experimental design, in particular by using a conceptual understanding test and attitude towards geometry questionnaire, in a public secondary school in Rangkasbitung, Banten, Indonesia. Two groups of students were used for data collection; the experimental (31 students) and the control groups (30 students). The data analyzed by independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Quantitative data illustrated that students' GAS scores have increased moderately from beginning to the end. This finding was in line with Khairiree (2020) and Auliya and Munasiah (2020) who found that use of augmented reality and geometry applications positively affected students' attitudes towards geometry.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Quantitative data illustrated that students' GAS scores have increased moderately from beginning to the end. This finding was in line with Khairiree (2020) and Auliya and Munasiah (2020) who found that use of augmented reality and geometry applications positively affected students' attitudes towards geometry.…”
Section: Discussionsupporting
confidence: 89%
“…Since the ODL process continues online and via computer, the effectiveness of a geometry teaching designed with this method and how it is perceived by students can be investigated more accurately. Furthermore, there are various studies that prove the positive results of applications such as dynamic software and AR technology in geometry lessons in terms of student learning in a regular face-to-face classroom environment at the elementary school level (Auliya & Munasiah, 2020;Dogruer & Akyuz, 2020); not encountered with ODL studies on this subject at the same level. Specifically, with the explosion of Covid-19 various studies reported about the educational activities during the outbreak (Baggaley, 2020;Lee et al, 2021), but very limited focus on specific issues.…”
Section: Why Geometry?mentioning
confidence: 99%
“…The level of spatial abilities of students is not high enough. The AR application enables faster comprehension of complex spatial problems and relationships (Auliya, & Munasiah, 2020) and allows improve spatial abilities. If students try to improve their spatial skills by AR training academic performance rate will be greater.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies examining the effect of material use on attitude in the framework of the research on attitudes towards geometry (Yemen, 2009;Budak, 2010;Önal and Demir, 2012;Şeker, 2014;Orçanlı, 2015;Sarıaslan and Küçük Demir, 2019;Topraklıoğlu, 2019;Özmen, 2019 ;Göksu, 2020;Frazier, 2020) and studies on determining the attitude towards geometry and whether it differed in terms of demographic characteristics (Bulut et al, 2002;Bindak, 2004;Aktaş and Aktaş, 2012;Mahanta, 2012;Hızlı, 2013;Sunzuma, Masocha and Zezekwa, 2013;Avcı et al, 2014;Melo and Martins, 2015;Kaba Daymaz and Boğazlıyan, 2016;Bora and Ahmed, 2018;Özdişçi, 2019;Ylano and Tayaben, 2019;Auliya and Munasiah, 2020;Bulut et al, 2020;Sevgi and Gürtaş, 2020;İlhan, Gemcioğlu and Poçan, 2021;Yücel and Koç, 2021) while studies on perceived school experiences usually centered on metaphor studies on school life Özdemir and Yüner, 2017;Arslan, 2020), on factors such as academic motivation and commitment to school (Finn, 1993;Arastam, 2009;Middleton and Midgley, 2002;Bozanoglu, 2004;Dogan, 2014;Fan and Williams, 2018) and on perceived school experiences in terms of demographic characteristics (Güler, 2019). Based on the relevant literature review, no research was found on the relationship between middle school students' attitudes towards geometry and their perceived school experiences.…”
Section: Introductionmentioning
confidence: 99%